Development of Human‐Like Advanced Coronary Plaques in Low‐Density Lipoprotein Receptor Knockout Pigs and Justification for Statin Treatment Before Formation of Atherosclerotic Plaques. Issue 4 (April 2016) - Li, Yuxin; Fuchimoto, Daiichiro; Sudo, Mitsumasa; Haruta, Hironori; Lin, Qing‐Fei; Takayama, Tadateru; Morita, Shotaro; Nochi, Tomonori; Suzuki, Shunichi; Sembon, Shoichiro; Nakai, Michiko; Kojima, Misaki; et al.
Abstract : Background: Although clinical trials have proved that statin can be used prophylactically against cardiovascular events, the direct effects of statin on plaque development are not well understood. We generated low‐density lipoprotein receptor knockout (LDLR −/− ) pigs to study the effects of early statin administration on development of atherosclerotic plaques, especially advanced plaques. Methods and Results: LDLR −/− pigs were generated by targeted deletion of exon 4 of the LDLR gene. Given a standard chow diet, LDLR −/− pigs showed atherosclerotic lesions starting at 6 months of age. When 3‐month‐old LDLR −/− pigs were fed a high‐cholesterol, high‐fat (HCHF) diet for 4 months (HCHF group), human‐like advanced coronary plaques developed. We also fed 3‐month‐old LDLR −/− pigs an HCHF diet with pitavastatin for 4 months (Statin Prophylaxis Group). Although serum cholesterol concentrations did not differ significantly between the 2 groups, intravascular ultrasound revealed 52% reduced plaque volume in statin‐treated pigs. Pathological examination revealed most lesions (87%) in the statin prophylaxis group were early‐stage lesions, versus 45% in the HCHF diet group ( P <0.01). Thin‐cap fibroatheroma characterized 40% of the plaques in the HCHF diet group versus 8% in the statin prophylaxis group ( P <0.01), intraplaque hemorrhage characterized 11% versus 1% ( P <0.01), and calcification characterized 22% versus 1% ( P <0.01). Conclusions: Results of our large animal experiment support statin prophylaxis before the occurrence of atherosclerosis. Early statin treatment appears to retard development of coronary artery atherosclerosis and ensure lesion stability. In addition, the LDLR −/− pigs we developed represent a large animal model of human‐like advanced coronary plaque suitable for translational research.